The Composition and Function of Pigeon Milk Microbiota Transmitted From Parent Pigeons to Squabs - Ding, Jinmei; Liao, Nan; Zheng, Yuming; Yang, Lingyu; Zhou, Hao; Xu, Ke; Han, Chengxiao; Luo, Huaixi; Qin, Chao; Tang, Chunhong; Wei, Longxing; Meng, He (Frontiers in Microbiology, 2020)
Mammalian neonates obtain antibodies, nutrients, and microbiota from breast milk that help them resist the complex growth environment. Similar to mammals’ lactation behavior for their offspring, parent pigeons regurgitate pigeon milk (PM) from their crops to feed the squabs. Whether pigeon milk is as valuable as mammalian milk is not clear, especially in terms of microbiota. This study adopted 16S rRNA gene sequencing to investigate the microbial composition and function in pigeon milk. We found abundant microbiota in pigeon milk. The dominant genera in parent pigeons’ milk were Lactobacillus, Enterococcus, Veillonella, and Bifidobacterium. An analysis of squab milk (SM) showed that Lactobacillus also accounted for a considerable proportion, followed by Bifidobacterium. Most of the squab milk microbial genera were also detected in parent pigeons. Microbial functional analysis showed that the squab milk microbes were more involved in the pathways of carbohydrate metabolism, amino acid metabolism, and energy metabolism. These findings indicated that microbiota play an important role in squabs and can be transmitted from parent pigeons to squabs by pigeon milk. The presence of plentiful probiotics in squabs also suggests that adding probiotics in artificial pigeon milk may promote the growth and development of squabs and improve the production performance of pigeons.